Architecture, Culture, Spirituality 7 - Tammy Gaber (International Institute of Islamic Thought, 2016)
Architecture, Culture, Spirituality (ACS) members Julio Bermudez (Catholic University of America, Washington DC), Norman Crowe (Professor Emeritus, Notre Dame School of Architecture), and Paul Tesar (North Carolina State University) co-chaired and organized the 2015 ACS symposium, which explored nature and the otherwise ordinary that form the spiritual foundations of architecture and culture. The symposium was held at Ghost Ranch, Abiquiu, NM, from June 18-21. Past ACS symposia have focused on various themes revolving around the ideas of creating and understanding sacred places. This year’s focus allowed researchers to discuss and critique nature’s important role and unraveling what has become “ordinary” as captured by Jalal al-Din Rumi’s quote: “Things are such, that someone lifting a cup, or watching the rain, petting a dog or singing, just singing – could be doing as much for this universe as anyone.” Of the fifty abstracts submitted, twenty-three made it through the blind peer-review process for presentation. Intentionally, ACS symposia have remained small in order to allow the formation of an intimate community of presenters, keynote speakers, and a small number of non-presenting attendees ...